“La educación emocional en los entornos virtuales” - Gancino Guaman, Blanca Zenaida (2021)
Nowadays, teachers and students of the Ecuadorian educational system are facing difficult situations in their academic training due to COVID-19. For this reason, the objective of this investigation is to determinate the emotional education in virtual environments through the workshops for the consolidation of teaching-learning process for students of seventh level from "Loja" Elementary School, 2020- 2021 period. The qualitative methodology applied was the kind of descriptive over in virtuality emotional education. In addition the method applied were the inductive and empirical where it is analyzed, interpreted and reflected the detailed information collected from the subjects, through the interview technique that showed children are unmotivated because they do not learn in the same way as in pre-specialization, while the teacher is concerned becuase most of students do not have connectivity for their classes. Consequently, the proposal was the making of workshop for encouraging the positive emotions in children through the active dynamics. This investigation will contribute to determine how, are teacher and student feel emotionally in virtual environments. Then, this is aspires to improve interpersonal relationships and understand the situation of each one. Regarding the results, it was identified that children express a negative emotion such as; sadness, boredom, anxiety, anger and shame. In conclusion, the virtuality emotional education is important since, they are two fundamental aspects of students, within the teaching-learning process.